MELISSA AFFICINALIS L AND ITS MEDICINAL PROPERTIES (Academicia Globe: Inderscience Research, 2022)
This article provides information about Melissa afficinalis L and its medicinal properties, chemical composition, research on it and preparation ofextracts from it.